Determining the fit of structural equation modeling of relationships between identity confusion and emotional breakdown based on the mediating role of defense mechanisms - Bagheri Masi Mordeh, Zahra; Zargham Hajebi, Majid; Habib Zadeh, Abbas (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the fit of structural equations of emotional breakdown based on identity confusion mediated by defense mechanisms. Methods: The research method was descriptive and the correlation research design was structural equation modeling. The statistical population of this study included the statistical population of this study including all adolescent female students with emotional failure in the 2019-20 academic year of Nurabad city. The sample of this study included 250 people who were selected using purposive sampling method. Data were collected using the Love Trauma Syndrome Questionnaire (Ross, 1999), the Personality Organization Questionnaire (Kernberg, 2002) and the Defense Mechanisms Questionnaire (Andrews et al., 1993). Research data were analyzed using Pearson correlation coefficient, structural equation model and SPSS software version 22 and AMOS version 22. Significance level in this study was considered 0.05. Results: The results showed that confusion had an indirect effect on emotional failure, so the existence of an indirect relationship between research variables is confirmed with 95% confidence (P